Stealing to Survive? Crime and Income Shocks in 19th Century France - Vincent Bignon; Eve Caroli; Roberto Galbiati (Institute for the Study of Labor (IZA), 2014)
Using local administrative data from 1826 to 1936, we document the evolution of crime rates in 19th century France and we estimate the impact of a negative income shock on crime. Our identification strategy exploits the phylloxera crisis. Between 1863 and 1890, phylloxera destroyed about 40% of French vineyards. We use the geographical variation in the timing of this shock to identify its impact on property and violent crime rates, as well as minor offences. Our estimates suggest that the phylloxera crisis caused a substantial increase in property crime rates and a significant decrease in violent crimes.
Keywords: K42; N33; R11; 330; crime; income shock; phylloxera; 19th century France